(untitled) (Homoeopathy for All, 2026)
Background: The introduction of the Competency-Based Dynamic Curriculum (CBDC) by the National Commission for Homoeopathy represents a major policy reform aligned with global trends in competency-based education (CBE) for health professions. While conceptually congruent with the holistic and individualised philosophy of homoeopathy, the CBDC has encountered significant implementation challenges. Objective: To critically analyse the current state of CBDC implementation in homoeopathy undergraduate and postgraduate programmes in India and to propose theoretically grounded, evidence-based strategies to enhance implementation success. Methods: This conceptual paper draws upon informal empirical insights from faculty experiences, contemporary literature on competency-based education, established educational theories, and lessons from medical education reforms in India. Results: Key challenges identified include limited faculty preparedness in edu cational methodology, inadequate institutional infrastructure, frag mented staffing models, superficial adoption of competency language, and absence of a structured faculty development framework. These factors collectively undermine the transformative potential of CBDC. Conclusion: The successful implementation of CBDC requires a shift from regulatory compliance to capacity building. Systematic faculty development, alignment of staffing and assessment policies, and institutional leadership engagement are essential to translate CBDC from policy intent into meaningful educational practice.